The Relationship between Family Ownership and Tax Avoidance: The Moderating Role of Business Ethical Commitment - Maulana Nanda; Arifin Rosid (Jurnal Dinamika Akuntansi, 2024)
Purposes: This study investigates the relationship between family ownership and tax avoidance, with business ethics commitment as a moderation. If well committed by the company, business ethics will improve the quality of decision-making in the business process and create ethical leadership that will carry an ethical practice. Methods: The study utilized regression analysis to examine the hypothesis in a sample of 110 companies listed on the IDX from 2016 to 2019. Findings: The results show that family-owned companies are not involved in tax avoidance and that a company’s commitment to business ethics can help reduce its tax avoidance practices. The interaction of business ethics commitment in family companies has no relationship with tax avoidance. This finding implies the importance of a company’s commitment to business ethics in running its business. Novelty: To the best of our knowledge, the nature of the relationship between business ethics commitment to tax avoidance and family ownership remains minimal. Thus, this study fills the research gap by further examining corporate tax avoidance practices determined by family ownership factors and testing the role of business ethics commitment with family ownership on tax avoidance.